Mouth control for a wheelchair - Sanabria-Salas, Joel (2023)
The proposed project consists of helping and contributing to the independence of translation for permanent wheelchair users who suffer from paralysis in their extremities and due to this they cannot operate or control the movement of electric wheelchairs that exist today in the day and must be assisted by another person for transportation, through a mouth control which will function as an air receiving device that will lead the air to pressure sensors connected to an Arduino circuit or integrated circuits which allows sending the movement signal to the chair and thus give an option of independence to the people involved.